2017
DOI: 10.5409/wjcp.v6.i1.69
|View full text |Cite
|
Sign up to set email alerts
|

Video recording of neonatal resuscitation: A feasibility study to inform widespread adoption

Abstract: AIMTo determine the feasibility of introducing video recording (VR) of neonatal resuscitation (NR) in a perinatal centre.METHODSThis was a prospective cohort quality improvement study on preterm infants and their caregivers. Based on evidence and experience of other centers using VR intervention, a contextually relevant implementation and evaluation strategy was designed in the planning phase. The components of intervention were pre-resuscitation team huddle, VR of NR and video debriefing (VD), all occurring o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…Gelbart et al reported that most staff members were willing to participate 20. Shivananda et al recently reported that 90% of questioned providers considered recording and reviewing acceptable 12. This suggests a growing base of evidence that recording and reviewing neonatal resuscitation is acceptable for neonatal care providers, supporting the recommendation for implementation made by the providers participating in our study.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Gelbart et al reported that most staff members were willing to participate 20. Shivananda et al recently reported that 90% of questioned providers considered recording and reviewing acceptable 12. This suggests a growing base of evidence that recording and reviewing neonatal resuscitation is acceptable for neonatal care providers, supporting the recommendation for implementation made by the providers participating in our study.…”
Section: Discussionsupporting
confidence: 72%
“…Enhanced learning after reviewing actual resuscitation was reported by Shivananda et al and Skåre et al 12 13. Many studies highlight the clear educational benefits of recording and reviewing actual care 14.…”
Section: Discussionmentioning
confidence: 90%
“…In the group with heart rate <100 bpm, time to heart rate ≥100 bpm was 132 (87-161) pre-vs. 110 (97-151) seconds post-implementation (p=0.99). The time to evaluate first heart rate was 17 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) pre-vs. 16 (12)(13)(14)(15)(16)(17)(18)(19)(20) seconds post-implementation, respectively (p=0.61) ( Table 2). Apgar scores at 5 minutes improved significantly from 7 (7-8) pre-to 8 (8-8) post-implementation (p=0.003) ( Table 1).…”
Section: Clinical Outcome Of the Resuscitated Newbornsmentioning
confidence: 99%
“…In an effort to improve training, numerous studies suggest "just-in-time" (just prior to procedure) and "justin-place" (within the clinical environment) simulation training may be an effective concept to improve clinical skills [10][11][12]. Video recording has been used to evaluate teamwork and guideline compliance during both simulated and real neonatal resuscitation and provided insights to targeted education [13][14][15][16][17]. Video may be a feasible method to assess performance and facilitate quality improvement [18].…”
Section: Introductionmentioning
confidence: 99%
“…Video recording captures more objective and consistent information than both retrospective and in-person documentation 2–4. However, technical and implementation barriers limit the reliability of video recording,5 as evident by the seven resuscitations excluded from our study due to incomplete recordings. A combination of both video recording and real-time documentation may provide the most complete and accurate method to document neonatal resuscitation.…”
Section: Discussionmentioning
confidence: 99%